The Prime Combination of Growing Media and Watering Frequency to the Growth of Sunflower Microgreens (Helianthus annuus L.) - Kuswati; Maudatus, Intan; Mudakir, Imam (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
Microgreens of sunflower (Helianthus annuus L.) are small and nutritious vegetables consumed at the early stages of growth. The growing process dictates the microgreen quality, such as planting media and watering frequency. This study aims to determine the interaction of various planting media with the watering on the microgreen growth parameters. This study conducts an experiment using 9 total treatments replicated 3 times. The research followed a randomized group design (RGD) and utilized analysis of variance (ANOVA) with a significance level of 5%, as well as Duncan's further test at a 5% significance level. The research parameters include plant height, hypocotyl length, epicotyl length, number of leaves, wet weight, consumable weight, and dry weight. The results showed that the interaction of planting media and watering frequency had a significant effect (P<0,01) on the growth parameters of sunflower microgreens. The best treatment combination is M1P3, Rockwool with watering three times a day with a plant height of 7,67 cm, hypocotyl length of 7,09 cm, epicotyl length 0.36 cm, number of leaves 2,53, wet weight 6,67 g, consumable weight 20.67 g and dry weight 1,22 g. Rockwool is sterile and has a structure that absorbs and stores water sufficiently for the growth of microgreens. The results of this study contribute significantly to improving the growth of sunflower (Helianthus annuus L.) microgreens through a combination of proper growing media and watering frequency.